395 Occupational safety and health challenges of an ageing workforce in Hong Kong. (20th November 2022) - Chan, Alan; Yau, Bonnie; Lam, Alice; Lo, Carol
Abstract : Background: With an ageing population, many governments encourage older persons to extend their working life with the wealth of work-related knowledge and experience. However, age-related changes in physical and cognitive status may affect their work capacity, work safety and health. We should pay attention to OSH issues for older employees and improve their ability to continue working. This study aims to identify the critical OSH problems and challenges of older employees, and propose strategies for encouraging them to remain in the workforce. Method: Quantitative surveys and focus groups were adopted. A total of 77 employees, employers, union representatives and experts were interviewed. 1, 225 employees were randomly selected to participate in the survey. Results: Psychological burden and perceived physical burden of older employees aged 55 and above were less than that of their younger counterparts. There was no significant difference in self-rated work ability between older and younger employees. Those who considered themselves working in a safer work environment were more inclined to stay in the workforce longer. OSH problems and challenges to employers, older employees, government and the society were identified, and relevant recommendations were proposed. Conclusion: Older employees were not significantly different from younger ones in work ability. OSH is critical to increasing older employees' intention to stay in the workforce that enables to sustain labour productivity. Learning Outcomes: This study examines the OSH problems and challenges faced by older employees across different industries in Hong Kong. It provides evidence for studies/practices in managing ageing workforce in different regions.